Complex Partial Seizure-Induced Transient Magnetic Resonance Change in SLE as First Manifestation (Annals of Medical Research, 2021)
None
Keywords: s : Magnetic resonance imaging, status epilepticus, partial epilepsy, cerebral edema, systemic lupus erythematosus.